The Micro-Politics of Strategy Formulation - Narayanan, V. K.; Fahey, Liam (Academy of Management Review, 1982)
The business policy literature traditionally has emphasized the rational and normative aspects of strategy formulation in organizations. This paper develops a framework to explicate strategic decision making from a political perspective, with particular reference to the evolution of coalitions around issues. The content of a strategic decision is posited as emerging from internal dynamics. The utility of the framework is demonstrated by its comparison with the rational model of strategic decision making.